Vitamin A Concentration in Cord and Maternal Serum and its Effects on Birth Weight - Barua, Dipi; Nasrin, Begum; Nahar, KN; Shamim, Shayela; Barua, Ashim Ranjan; Begum, Firoza (Bangladesh Journal of Child Health, 2010)
Introduction: Birth weight is a reliable index of intra-uterine growth and a major factor determining child survival, future physical growth and mental development. Objectives: The present study was designed to explore the association of maternal serum as well as cord serum vitamin A level with birth weight. Materials and Methods: This prospective randomized study was carried out in Maternity and Child Health Training Institute (MCHTI), Azimpur, Dhaka during the period from January to July, 2002 on 100 healthy pregnant mothers of 38-40 weeks of gestation and on 100 new born babies born to these mothers. Results: Mean birth weight was 2804 gm (±43.1) with a range of 1600-3900 gm. Cord serum vitamin A level was 583 (±1.73) μg/dl with a range of 4.9-102.04 μg/dl, while maternal serum vitamin A level was 53.5μg/dl (±1.5) with a range of 17.2-89.2 μg/dl. Newborn having birth weight ≥ 2500gm was found to have higher level of maternal serum vitamin A than the newborn having weight <2500gm, (54.5±1.6 μg/dl vs 49.4±3.04 μg/dl, p=.06) but the difference was not statistically significant. There was no significant difference in cord serum vitamin A level between two groups of newborn (57.8±2.06 μg/dl vs. 60.2±2.03 μg/dl, p=.2). Key words: Vitamin A concentration; birth weight. DOI: 10.3329/bjch.v33i2.5676 Bangladesh Journal of Child Health 2009; Vol.33(2): 46-49